Hubungan Penggunaan Media Sosial, Jenis Kelamin, dan Teman Sebaya Terhadap Perilaku Bullying pada Anak Kelas XI SMAN 5 Mataram Nusa Tenggara Barat - Nurhafizhah Nurhafizhah; Dian Rahadianti; Lusiana Wahyu Ratna Wijayanti; Alfian Muhajir (Malahayati Nursing Journal, 2026)
ABSTRACT Bullying is an aggressive behavior carried out repeatedly and is one form of violence that frequently occurs in the school environment, making it a serious concern in the field of education. This phenomenon is a major problem among senior high school adolescents because it has negative impacts on mental, social, and academic health. To determine the relationship between social media use, gender, and peer influence on bullying behavior among eleventh-grade students at SMAN 5 Mataram, West Nusa Tenggara. This study was a quantitative analytical observational study with a cross-sectional design. The study population consisted of all eleventh-grade students at SMAN 5 Mataram, totaling 445 students. The sample included 95 respondents selected using stratified random sampling. Data were collected using questionnaires, namely the Adolescent Peer Relations Instrument (APRI) to measure bullying behavior, as well as questionnaires on social media use, gender, and peer influence. Data analysis was conducted using univariate and bivariate analyses to determine relationships between research variables. Most respondents were 16 years old (56.84%), male (52.6%), and had parents with elementary school education as the highest educational level (30.53%). Moderate social media use was reported by 49.50% of respondents, low peer influence by 37.9%, and almost all respondents had experienced bullying behavior (52.6%). There is a relationship between social media use, gender, and peer influence with bullying behavior among eleventh-grade students at SMAN 5 Mataram. Keywords: Bullying, Social Media, Gender, Peers.  ABSTRAK Bullying merupakan perilaku agresif yang dilakukan secara berulang kali dan salah satu bentuk kekerasan yang kerap terjadi di lingkungan sekolah, menjadi perhatian serius dalam dunia pendidikan. Fenomena ini menjadi masalah serius pada remaja sekolah menengah atas karena berdampak negatif terhadap kesehatan mental, sosial, dan akademik. Untuk mengetahui hubungan antara penggunaan media sosial, jenis kelamin, dan pengaruh teman sebaya terhadap perilaku bullying pada siswa kelas XI SMAN 5 Mataram, Nusa Tenggara Barat. Penelitian kuantitatif analitik observasional dengan rancangan cross sectional. Populasi penelitian adalah seluruh siswa kelas XI SMAN 5 Mataram sebanyak 445 siswa. Sampel penelitian berjumlah 95 responden yang dipilih menggunakan metode random sampling. Data dikumpulkan menggunakan kuesioner, yaitu Adolescent Peer Relations Instrument (APRI) untuk mengukur perilaku bullying, serta kuesioner penggunaan media sosial, jenis kelamin, dan pengaruh teman sebaya. Analisis data dilakukan secara univariat dan bivariat untuk mengetahui hubungan antar variabel penelitian. Responden penelitian sebagian besar berusia 16 tahun (56,84%), berjenis kelamin laki-laki (52,6%), pendidikan orang tua sebagian besar lulusan SD (30,53%), penggunaan media sosial sedang (49,50%), teman sebaya rendah (37,9%), dan perilaku bullying  (52,6%). Terdapat hubungan antara penggunaan media sosial, jenis kelamin, dan teman sebaya dengan perilaku bullying pada siswa kelas XI SMAN 5 Mataram.  Kata Kunci: Bullying, Media Sosial, Jenis Kelamin, Teman Sebaya.